PUBLIC DEBT DETERMINANTS IN ALBANIA - Edlira Kalaja; Arjeta Vokshi (Journal of Process Management and New Technologies, 2015)
State budget is one of the most important instruments where the government reflects its future policies, priorities and commitments. Its reading in recent years clearly shows the increased size of public debt beyond the upper limit of 60% of GDP, in many countries including Albania. This fact constitutes analarming trend signaled even by many international financial institutions. However, the worldwide increasing levels of budget deficits and public debtsare not accidental. Through this article we aim to explore the relationships that exists between different determinants such as governance, social and economic variables that directly affect the size of public debt in Albania, where demographic factors are noted as the main contributors, followed by political systems along with various economic developments that the country has experienced in years.